EFFECT OF BIOFERTILIZERS AND SALICYLIC ACID ON AVAILABILITY OF SOME NUTRIENTS IN SOIL AND PLANT AND SOME VEGETATIVE AND PRODUCTION QUALITY OF BEANS IRRIGATED WITH SALINE WATER - & et al., Alwan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The aim of this study which have been implemented in the AL-mada,an area 40 km southeast of Baghdad in the silty loam soil to evaluate of interaction effect between inoculant with biofertilizers and salicylic acid on Iron  and Manganese availability in soils and concentration in leaves and some vegetative growth indicators As well as flowers and quantitative specifications production quantity of plant Beans when irrigation with river and drainage water, the experiment Carried out by using Spilt-Spilt-Plot Design it was treatment of irrigation is the main plot while the treatment of spraying with salicylic acid is sub -plots plots while the treatment of bio-fertilizers are placed  under. sub -plots. The triple combination treated between river water, biofertilizer mixture and 0.5mM from salicylic acid W1B3S1 recorded highest values in the concentration of Iron and Manganese availability in soils when recorded (21.65and 21.28) mg.kg-1 and (12.83and 12.57) mg.kg-1 and concentration of same elements in leaves recorded (258.4 and 240.3) mg.kg-1 and (217.0 and 212.3) mg.kg-1  and concentration of chlorophyll (20.54and 19.31)mg.g-1  and total dry matter in shoots  (34.73and 31.12)g.plant-1 and flowering date (33.00 and 32.67) day and total number of  flowers (127.7and 121.0) flower.plant-1  and early production (9.31and 9.25) ton. Ha-1  further more  total production (37.24and 35.14) ton. Ha-1. Treatment W1S2B3 achieved the lowest values in sodium and Chlorine concentration (0.25 and 0.22) and (1.45 and 1.35) for both of them in tow growing season respectively .